The hazards of Nomenclatural Archaeology? The Diptera names of Theodorus van Swinderen in his 1822 Index Rerum Naturalium quae conservantur in Museo Academico Groningano - Evenhuis, Neal L. (Zootaxa, 2020)
The Diptera names listed by Theodorus van Swinderen in his list of animals and minerals in the Groningen Natural History Museum are itemized and annotated. Most of the names listed, including those newly proposed, are synonymous with previously published names. One (Sarcophaga Swinderen, 1822) is a senior synonym of the well-known Sarcophaga Meigen, 1824. It has been dealt with in a previous paper, and Sarcophaga Swinderen, 1822 is now declared a nomen oblitum. The following new synonymies are proposed herein: Acolasta Swinderen, 1822 = Sepedon Latreille, 1804, n. syn. [Sciomyzidae]; Cleona Swinderen, 1822 = Callomyia Meigen, 1804, n. syn. [Platypezidae]; Cleona acuminata Swinderen, 1822 = Callomyia elegans Meigen, 1804, n. syn. [Platypezidae]; Driope Swinderen, 1822 = Dorycera Meigen, 1830, n. syn. [Ulidiidae]; Macrostoma Swinderen, 1822 = Volucella Geoffroy, 1762, n. syn. [Syrphidae]; Marsupium Swinderen, 1822 = Sphegina Meigen, 1822, n. syn. [Syrphidae]; Nycteria Swinderen, 1822 = Pipiza Fallén, 1810, n. syn. [Syrphidae]; Pacystoma Swinderen, 1822 = Medetera Fischer von Waldheim, 1819, n. syn. [Dolichopodidae]; Penthesilia Swinderen, 1822 = Merodon Meigen, 1803, n. syn. [Syrphidae]; Tromera Swinderen, 1822 = Madiza Fallén, 1810, n. syn. [Milichiidae]. Titania Swinderen, 1822 (preoccupied by Titania Meigen, 1800) and its type species Titania albipennis Swinderen, 1822 are available names, but are considered here as nomina dubia and unplaced within Diptera. Thericas Swinderen, 1822 is considered unavailable as it is not accompanied by a description or a definition and is based on an unavailable name. Dorycera Meigen, 1830 is declared a nomen protectum and Driope Swinderen, 1822 is declared a nomen oblitum; Medetera muralis Meigen, 1824 is declared a nomen protectum and Pacystoma muralis Swinderen, 1822 a nomen oblitum.